Utilizing Targeted Next-Generation Sequencing for Rapid, Accurate, and Cost-Effective Pathogen Detection in Lower Respiratory Tract Infections - Qin L; Liang M; Song J; Chen P; Zhang S; Zhou Y; Li H; Tang J; Ma Y; Yang B; Xu J; Zhang J (Infection and Drug Resistance)
Lisha Qin,1,* Mengyuan Liang,1,2,* Jianping Song,1,* Ping Chen,1,* Shujing Zhang,3,* Yaya Zhou,1 Hui Li,1 Jian Tang,1 Yanling Ma,1 Bohan Yang,1 Juanjuan Xu,1 Jianchu Zhang1 1Department of Respiratory and Critical Care Medicine, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Zhengzhou University People’s Hospital, Henan Provincial People’s Hospital, Zhengzhou, People’s Republic of China; 3Department of Pediatrics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianchu Zhang, Department of Respiratory and Critical Care Medicine, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China, Tel +86-13971445469, Email zsn0928@163.comObjective: To evaluate the diagnostic performance and clinical impact of targeted next-generation sequencing (tNGS) in patients with suspected lower respiratory tract infections.Methods: Following propensity score matching, we compared the diagnostic performances of tNGS and metagenomic next-generation sequencing (mNGS). Furthermore, the diagnostic performance of tNGS was compared with that of culture, and its clinical impact was assessed.Results: After propensity score matching, the coincidence rate of tNGS was comparable to that of mNGS (82.9% vs 73.9%, P=0.079). The detection rates for bacterial, viral, fungal, and mixed infections were not significantly different (P> 0.05). Bacterial-viral co-infection (16.7%) was the most common mixed infection detected by tNGS. tNGS showed a higher detection rate than culture (75.2% vs 19.0%, P< 0.01). The positive detection rate by tNGS was not significantly different between immunocompromised and immunocompetent patients (88.6% vs 80.5%, P=0.202), but was significantly higher than that by culture (P< 0.001). Moreover, 65 patients (44.5%) had their medications modified based on the tNGS results, and the majority exhibited notable improvement regardless of treatment adjustment.Conclusion: tNGS performs comparably to mNGS and surpasses culture in detecting lower respiratory tract infections. Nevertheless, tNGS is faster and more cost-effective than mNGS, making it highly significant for guiding rational treatment.Keywords: targeted next-generation sequencing, metagenomic next-generation sequencing, lower respiratory tract infections, diagnosis, antibiotic treatment